Maritime Safety Culture Development and Incident-Based Learning Integration in Vocational Competency Assessment - Nafi Almuzani; Irfan Faozun; Natanael Suranta; Chanra Purnama (International Journal of Educational Practice and Policy, 2026)
Maritime safety remains critically dependent on the quality of vocational competency assessment, yet current assessment systems predominantly evaluate procedural compliance rather than the safety culture dispositions and incident-informed judgment that prevent maritime accidents. This study investigates how safety culture development and incident-based learning can be integrated into vocational competency assessment within Indonesian maritime education. Employing a qualitative design, semi-structured interviews were conducted with 12 maritime safety and assessment experts, 18 maritime vocational lecturers, and 15 recent graduates across three maritime polytechnic institutions. Data were analyzed through thematic analysis with open and axial coding, cross-group comparison, and narrative synthesis leading to framework derivation. Five themes emerged: the procedural–dispositional assessment gap, incident knowledge as a pedagogical resource, safety culture as an assessable competency dimension, the psychomotor–cognitive–affective integration challenge, and institutional barriers to incident-based learning implementation. Cross-group analysis revealed that experts prioritized safety disposition assessment, lecturers emphasized standardization constraints, and graduates reported that their safety competence was tested through recall-based examinations bearing limited resemblance to the judgment-intensive safety decisions professional practice demanded. The study contributes a safety-integrated competency assessment framework positioning safety culture and incident-informed reasoning as structurally assessable dimensions alongside procedural proficiency.